01 What is seronegative MG? analysis of the Northern Irish MG population. Issue 3 (15th February 2011) - Carr, A; McCartan, D R; Leite, M I; Vincent, A; Cardwell, C; McCarron, P O; O'Reilly, D; McConville, J
Abstract : Background: Seronegative MG (SNMG) is the proportion of autoimmune MG without detectable pathogenic antibodies to AChR or MuSK on radio-immunoprecipitation or recently developed cell-based assays. The effect of the application of these new assays on frequency and characteristics of SNMG in a complete MG population is not known. Methods: A population-based epidemiological study of myasthenia gravis in Northern Ireland (NI) between 01/01/2000 and 31/12/2008 was performed. Patients were categorised clinically and serologically using radio-immunoprecipitation (AChR ab, MuSK ab) and cell-based immunoflourescence assays (MuSK and AChR clustered with rapsyn). The characteristics of SNMG were examined. Results: MG incidence rate (IR) in NI was 13.9 (95%CI: 12.2 to 15.8) cases per million person years. Fifteen cases (7.1%) remained seronegative. Mean (S.D.) age 59.1 (22.5) years; M:F ratio=1.1:1; Mean (S.D.) MGFA severity score 2.0 (1.2). 33% had ocular-only symptoms. No differences were found when compared with AChR MG at 5% significance level. Conclusion: Compared with the distribution of other recognised MG subpopulations, SNMG is indistinct and broadly distributed. There are no recognisable subsets within the NI seronegative cohort. This epidemiological data is consistent with SNMG being either a heterogeneous population or an epiphenomenon resulting from false-negative antibody assays or false-positive diagnoses.